ELECTRIC STUNNING OF CATTLE FOR SLAUGHTERING AND SECURING THE BEEF FROM MICROORGANISM - Wayan Sayang Yupardi; I Made Nuryasa; Ni Luh Putu Sriyani; Eny Puspani; I Gede Suranjaya (International Journal of Biosciences and Biotechnology, 2016)
Stunning electricity current of 1.0 A, 200 – 300 V were caused the destruction of cattle’s centralnerve. This is very important to drain blood as much as possible from the whole body. Thiscauses its beef not become a media of unexpected microorganism to develop theirself.In themodern age right now, electricity is needed much for living on the earth or outer space. In otherwords, live is much depend on it. Indonesia is a tropical and agricultural country with highhumidity. These are good media for microorganism to develop theirself i.e. in aerobic conditionsuch as Pseudomonas, Achromobacter (induce rancidity in), Strepcococcus, Leuconostoc,Bacillus (causes mucus on beef surface), Lactobaccillus (causes the changes of beef colour fromred to greenish), Photobacterium (causes phosphorescent). anaerobic codition Achromobacterand Proteus cause sour taste. The beef or other food stuff become spoiled fast if they are notpreserved in low temperatureIt is necessary to control the room temperature. The objectives ofthis study were to know and open insight about physiological works of electricity in order toprovide healthy beef as a source of animal protein to form a bright nation. The beef can bepreserved more than 30 days without decreasing its hygiene level in the temperature of 5 – 7oC.At these low temperatures the microorganism mentioned above can delayed their growth anddevelopment.